A compact dual wavelength ring laser using a semiconductor optical amplifier and array waveguide grating - Ahmad, Harith; Thambiratnam, K.; Harun, Sulaiman Wadi; Sulaiman, Abdul Hadi; Aziz, Siti Narimah (INOE, 2008)
It is demonstrated a stable dual-wavelength fiber ring laser using an SOA in conjunction with an array waveguide grating (AWG). The experimental results show stable dual lasing lines with an adjustable wavelength separation and a SNR of over 30 dB under room temperature. The first channel operates at 1530.2 nm laser wavelength with an output power of approximately -11 dBm at a saturation current of 150 mA. The second channel operates at either 1532.8 nm or 1538.8 nm with a maximum output power of more than -24 dBm. By changing the ports of the AWG, the center wavelengths of the two lasing lines and wavelength separation can be tuned under room-temperature.